2007
DOI: 10.1071/rdv19n1ab5
|View full text |Cite
|
Sign up to set email alerts
|

5 Nucleolar Development Requires Transcriptional Activity During Porcine Embryonic Genome Activation

Abstract: The development of a functional nucleolus accompanying the major embryonic genome activation (EGA) is considered a marker for embryo quality and viability. However, the use of this marker is limited by the lack of accurate knowledge of the biology of embryonic nucleologenesis. The objective of this study was to elucidate the role of RNA polymerase I (RPI) and total transcriptional activity, reflecting EGA, for nucleologenesis in in vivo-developed porcine embryos. Late 4-cell-stage embryos were cultured in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…For the first time ever this finding was confirmed by experiments from this group. We, as the first, have confirmed the selective inhibition of RNA pol I by this concentration and time interval outcoming from the previous experiments by bovine (Svarcova et al 2007a) and swine embryos (Svarcova et al 2007b). As was proved earlier, for future successful development, embryos necessarily need ribosomes (Laurencik et al 2003).…”
Section: Effect Of Actinomycin Dsupporting
confidence: 62%
See 4 more Smart Citations
“…For the first time ever this finding was confirmed by experiments from this group. We, as the first, have confirmed the selective inhibition of RNA pol I by this concentration and time interval outcoming from the previous experiments by bovine (Svarcova et al 2007a) and swine embryos (Svarcova et al 2007b). As was proved earlier, for future successful development, embryos necessarily need ribosomes (Laurencik et al 2003).…”
Section: Effect Of Actinomycin Dsupporting
confidence: 62%
“…The importance of EGA in further embryo development, including the importance of de novo nucleolar formation related to particular activation of RNA pol I transcription (Laurincik et al 2000(Laurincik et al , 2003Pivko et al 2004;Svarcova et al 2007bSvarcova et al , 2008, was reported in previous studies from this group. On the other hand, as was shown by specific inhibition transcriptional activation of RNA pol II and III, activity of RNA pol I is not sufficient for formation of fully functional nucleoli in early embryos (Svarcova et al 2007a).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations